A Qualitative Study on Risk Factors Contributing to Stunting in Karang Dima Village, Sumbawa Regency - Yunita Lestari; Has'ad Rahman Attamimi; Evi Gustia Kesuma; Hajera Hajera (International Journal Of Health Science, 2025)
Stunting is a significant public health issue with lasting effects on human development and the quality of the workforce. This study aimed to identify the risk factors of stunting using an epidemiological approach in Karang Dima Village, Sumbawa Regency. A descriptive qualitative method was employed, and data were gathered through in-depth interviews with 22 mothers of stunted children and environmental observations. The results highlighted several key factors contributing to stunting. Host factors, such as low maternal nutritional knowledge, improper parenting practices, and limited spousal support during pregnancy, were identified as primary contributors. These factors negatively influence a mother’s ability to provide adequate care and nutrition during pregnancy and the early stages of a child’s life. Agent factors included recurrent infections, including diarrhea, acute respiratory infections (ARI), and measles. These infections, often linked to weak child immunity, exacerbate the risk of stunting, especially when compounded by poor nutritional intake. Environmental factors also played a significant role. Poor sanitation, high population density, and exposure to pollution from household waste burning and indoor cigarette smoke were noted as critical elements in the village’s stunting risk profile. These environmental conditions compromise both maternal and child health, increasing vulnerability to infections and impairing overall development. The study emphasizes that stunting prevention requires a comprehensive, multi-faceted approach. Nutritional education, improved sanitation, and greater family involvement, particularly from fathers and extended family members, are essential in reducing stunting risk. The findings highlight the need for cross-sectoral strategies to address the various interrelated factors contributing to stunting, particularly in vulnerable communities. Accelerating stunting reduction efforts requires a collaborative, community-driven approach involving healthcare providers, local governments, and families.